Multiple Magnetic Phases and Anomalous Hall Effect in Sb1.9Fe0.1Te2.85S0.15 Topological Insulators - Pal D.; Verma A.; Alam M.; Dan S.; Kumar A.; Yusuf S.M.; Banik S.; Chakravarty S.; Saha S.; Patil S.; Chatterjee S. (My University, 2025)
Due to fundamental and technological concerns, investigating materials with topological magnetic structures has always been a focus of significant research. We explored Sb1.9Fe0.1Te2.85S0.15 where a unique combination of disordered glassy phases, competitive FM-AFM interactions, and nontrivial surface state coexisted at the same time. We have discussed the impact of those complicated magnetic phases upon the observed AHE in Sb1.9Fe0.1Te2.85S0.15 with magneto-transport studies. The AC susceptibility results demonstrate a shift in the freezing temperature with excitation frequency, the comprehensive analysis verifies the slower dynamics, and a nonzero Vogel-Fulcher temperature T0 suggests cluster spin glass. This, together with an intermediate value of the Mydosh parameter, provides an evidence for the formation of a cluster spin glass state in the present system. Topological frustrated magnets, which can host both magnetic frustrations and Dirac quasi-particles, are highly sought after class of compounds. Furthermore, as seen by the de Haas-van Alphen (dHvA) oscillation study, the fermiology deviates with doping and produces multiple Fermi pockets, revealing a rich complexity in the underlying electronic structure. © 2023 American Chemical Society.